The Burden of Road Traffic Injuries in Yazd Province - Iran - Mahmood Vakili; Mohsen Mirzaei; Azar Pirdehghan; Mohamadreza Sadeghian; Majid Jafarizadeh; Mojtaba Alimi; Shadi Naderian; Arezoo Aghakoochak (Bulletin of Emergency and Trauma, 2016)
Objectives: To estimate the Disabled-adjusted Life Years (DALYs) of Road Traffic Accidents in patients referred to hospitals in Yazd Province, central Iran. Methods: This cross-sectional study was conducted in Yazd province during 2010. To calculate the Years of Life Lost (YLL) due to premature death and to calculate the incidence of non-fatal injuries and Years Lost due to Disability (YLD), the data were collected from Yazd death registration system and hospital records. The causes of death and nature of non-fatal injuries were classified using International Classification of Diseases (ICD-10). We estimated Disability Adjusted Life Years (DALYs) on the guidelines of the Global Burden of Disease Study (discount rate: 0.03, age weight: 0.04, constant age weight correction factor: 0.165). Age and sex composition was taken from the National Statistical Center for the year 2010. Results: During 2009, 483 deaths were caused by traffic accidents in Yazd Province, 382 (79.09%) of which were males, and 101 (20.91%) were females. The mortality rates for males and females were 70.98 and 20.15 in 100,000, respectively. The years of life lost due to premature deaths were 15.84/1000 in men and 4.75/1,000 in women. Total YLLs caused by traffic accidents were 10,908 years . The injuries caused by traffic accidents were calculated as 15.21 and 3.73/1,000 in males and females, respectively. The total YLDs was calculated 1.51/1,000. The total burden of Road Traffic Injuries in Yazd province was 12478 years (DALYs), 87.41% of which was due to premature death, and 12.59% was related to disability. Also, 78.32% was lost in males. The age specific peak of burden was in 15-29 year. Conclusion: This study showed that traffic accidents in Yazd impose a high burden. It seems that it is one of the health sector priorities. It is recommended to revise laws on use of motorcycles, especially on helmet use for motorcyclists, enforce strict laws in residential areas, and review social determinant affecting the incidence of such accidents.